The Effects of Parenting and Temperament Similarity Among Adolescent Siblings on Positive Family Relationships - Shi, Xinxin; Campione-Barr, Nicole (Frontiers in Psychology, 2021)
The detrimental effects of parental differential treatment have been shown in previous research (Coldwell, Pike, & Dunn, 2008), but fewer researchers have pointed out that differential treatment does not always lead to negative outcomes (Kowal & Kramer (1997). Thus, the present study examines the role of temperament similarity on the association between parenting similarity and positive family relationship qualities over 1 year in 145 adolescent sibling dyads (Mfirst-born = 14.97, SD = 1.68 years; Msecond-born = 12.20, SD = 1.92 years). Latent moderator structure models (LMS) showed that higher level of parenting similarity was related to more positive family relationships when siblings were more similar in their temperaments; however, lower level of parenting similarity was related to more positive relationship qualities with family members one year later in the context of less sibling temperament similarity.